2007
DOI: 10.1186/1476-069x-6-2
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of serum concentrations of organochlorine compounds in Swedish pregnant women: a cross-sectional study

Abstract: Background: We performed a cross-sectional study of associations between personal characteristics and lipid-adjusted serum concentrations of certain PCB congeners and chlorinated pesticides/metabolites among 323 pregnant primiparous women from Uppsala County (age 18-41 years) sampled 1996-1999.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
64
4
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(87 citation statements)
references
References 30 publications
17
64
4
2
Order By: Relevance
“…Older age predicted higher serum PCB levels. This is consistent with what other researchers have noted as indicative of the accumulation of exposure (Furberg et al, 2002) and/or a cohort effect whereby younger women have less exposure to PCB because of decreasing PCB use and levels in the environment (Glynn et al, 2007). Lopez-Carrillo et al (2001) found that breast-feeding is a route for the excretion of metabolites and that 1-2 years of lactation could reduce DDE serum levels in mothers by 50%.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Older age predicted higher serum PCB levels. This is consistent with what other researchers have noted as indicative of the accumulation of exposure (Furberg et al, 2002) and/or a cohort effect whereby younger women have less exposure to PCB because of decreasing PCB use and levels in the environment (Glynn et al, 2007). Lopez-Carrillo et al (2001) found that breast-feeding is a route for the excretion of metabolites and that 1-2 years of lactation could reduce DDE serum levels in mothers by 50%.…”
Section: Discussionsupporting
confidence: 78%
“…In our study, the number of total months that a woman had breast-fed her children was also inversely associated with serum PCB levels, consistent with this route as an efficient means of excretion from the mother but a substantial source of exposure for the infant. Some studies have found an inverse association between pre-pregnancy BMI and serum PCB levels in pregnant women (James et al, 2002;Glynn et al, 2007). Glynn et al (2007) attribute this to a dilution effect associated with the rapid weight gain during pregnancy, which might be greater in those with high BMI to begin with.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Huisman et al (1995) indicated this as one of the reasons why food intake explained only a small fraction of the variance of cord blood PCB and dioxin levels in 355 women. Recently, Glynn et al (2007) found OC levels measured in Swedish pregnant women, were indeed influenced by fatty fish consumption years before pregnancy, namely during adolescence. We noticed that significantly more residents from rural areas reported consumption of local diary products (25%) and of locally produced animal fat (41%) compared with the whole population (respectively 13% and 17%).…”
Section: Determinants Of Pollutant Levels In Cord Bloodmentioning
confidence: 98%
“…Age was a significant determinant of serum concentration of chlorinated pesticides in this study. Glynn et al (2007) also reported another serum concentration of the general Swedish population (Glynn et al, 2007). The serum of 323 pregnant primiparous women living in Uppsala county (age 18-41 years) sampled in 1996-1999.…”
Section: Levels In the European Population 441 Swedenmentioning
confidence: 99%